Cognitive behavioral therapy with adaptive virtual reality exposure vs. cognitive behavioral therapy with in vivo exposure in the treatment of social anxiety disorder: A study protocol for a randomized controlled trial - Ørskov, Per Trads; Lichtenstein, Mia Beck; Ernst, Mathias Torp; Fasterholdt, Iben; Matthiesen, Asge Frederik; Scirea, Marco; Bouchard, Stephane; Andersen, Tonny Elmose (Frontiers in Psychiatry, 2022)
Background: Social anxiety disorder (SAD) has a high prevalence and an early onset and with recovery taking decades to occur. Current evidence supports the efficacy of cognitive behavioral therapy (CBT) with virtual reality (VR) exposure. However, the evidence is based on a sparse number of studies with predominantly small sample sizes. There is a need for more trials investigating the optimal way of applying VR based exposure for SAD. In this trial, we will test the efficacy of CBT with adaptive VR exposure allowing adjustment of the exposure based on real-time monitoring of the participants´s anxiety level. Methods: The trial is a randomized controlled, assessor-blinded, parallel-group superiority trail. The study has two arms: 1) CBT including exposure in vivo (CBT-Exp), 2) CBT including exposure therapy using individually tailored VR-content and a system to track anxiety levels (CBT-ExpVR). Treatment is individual, manual-based and consists of 10 weekly sessions with a duration of 60 minutes. The study includes 90 participants diagnosed with SAD. Assessments are carried out pre-treatment, mid-treatment and at follow-up (6 and 12 months). The primary outcome is the mean score on the Social Interaction Anxiety Scale (SIAS) with the primary endpoint being post-treatment. Discussion: The study adds to the existing knowledge by assessing the efficacy of CBT with adaptive VR exposure. The study has high methodological rigor using a randomized controlled trial with a large sample size that includes follow-up data and validated measures for social anxiety outcomes. Trial registration: ClinicalTrials.gov NCT05302518